The Influence of Digital Literacy Classes with QR-Code Media on Fast Food Eating Habits in Obese Adolescents - de Frites, Chairani Riski; Simbolon, Demsa; Linda (Futurity Medicine, 2024)
Nutritional problems can affect cognitive ability, productivity, and performance in adolescents. Therefore, it is crucial to address obesity among adolescents. Aims: This study explores the impact of digital literacy interventions using QR-Code media on changing fast food consumption habits among obese adolescents at SMAN 6 Bengkulu City. Methodology: This study uses a pre-experimental method with the One Group Pre-Test and Post-Test method. It involves student classes X and XI using purposive sampling (n=41). The Wilcoxon Signed Rank test and McNemar test were used for analysis. Results: Research results show that existence influences significant digital literacy toward understanding obesity and eating habits (p-value = 0.0001). Scientific Novelty: This research is unique in that it applies digital literacy interventions using QR-Code media to enhance understanding and awareness of healthy dietary choices, aimed at changing fast food consumption habits among obese adolescents. Conclusion: Digital literacy significantly impacts understanding and habits of teenager obesity.